Pertumbuhan Dan Hasil Beberapa Varietas Tanaman Kubis Bunga (Brasica Olercea Var. Bathysl.) Pada Dataran Menengah - Widodo, R Wahyono; Somantri, Asep (Fakultas Pertanian Universitas Winaya Mukti, 2023)
Field experiments were carried out in Nangklong village, Maripari village, Cibatu sub district, Garut district with an altitude of 764 m above sea level from September 2020 to November 2020. The purpose of this experiment was to study the growth and yield of several varieties of cauliflower (brasica olercea var. bathysl.) in the middle plains. The experiment was conducted using a randomized block design with 5 replications. The treatments consisted of: A (Bima 45), B (Kaila), C (PM 126), D (Provita) and E (Aquina). The experimental results showed that the growth and yield of several varieties of cauliflower were different in the middle plains. The Bima 45 variety showed higher growth and yield of cauliflower compared to other varieties in the middle plains. The Bima 45 variety produced a cabbage weight of 20.68 kg plot1 or equivalent to 40.17 tons ha1.